If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(n) = 7 + (n + -1)(4) Multiply a * n an = 7 + (n + -1)(4) Reorder the terms: an = 7 + (-1 + n)(4) Reorder the terms for easier multiplication: an = 7 + 4(-1 + n) an = 7 + (-1 * 4 + n * 4) an = 7 + (-4 + 4n) Combine like terms: 7 + -4 = 3 an = 3 + 4n Solving an = 3 + 4n Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by 'n'. a = 3n-1 + 4 Simplifying a = 3n-1 + 4 Reorder the terms: a = 4 + 3n-1
| a(n)=7 | | -6+8(x-4)=12x+3-4x | | y+5=7(x+8) | | x(x+x)=4(4+5) | | .2x^2+12=3.4 | | 5(x+2)=12-3x | | x=1/2(110) | | ln(x+1)=x-0.8 | | Ln(x^2-25)=ln(-5x-1) | | 24x^2=180 | | Ln(x^2)=ln(-5x-1) | | 5(7n-4)+4=12+7n | | 2x+3z=2+5y | | 9n-8=-458 | | 9a-8=-260 | | 6n-5=271 | | 4p+8=-120 | | 27x^2-4=0 | | 3b+9=150 | | 50*50+140*140=x*x | | 2a=-38 | | 2x^2-12=-5+x | | x=1/2(80+60) | | 38-6n=4(-4n+3)-4 | | 4p=-164 | | x(x+4)+x(2+x)=x(2x)+12 | | -7a=-252 | | -t^2-13t=0 | | -39+6r=3+5(6+3r) | | x=1/2(40) | | -5j=250 | | 2(3x-2)-5(x-1)=1(3) |